Both Systemic and Pulmonary Artery Stiffness Predict Ventricular Functional Recovery after Successful Percutaneous Closure of Atrial Septal Defects in Adults. (11th November 2015) - Baykan, Ahmet Oytun; Gür, Mustafa; Acele, Armağan; Şeker, Taner; Yüksel Kalkan, Gülhan; Şahin, Durmuş Yıldıray; Koc, Mevlüt; Bulut, Atilla; Harbalıoğlu, Hazar; Caylı, Murat
ABSTRACT: Background: Percutaneous closure of atrial septal defect (ASD) has become the preferred method in treatment of the majority of cases. The aim of this study was to evaluate the echocardiographic effects of percutaneous closure of secundum ASD in adults and assess which parameters predict good response to closure. Design: We prospectively included 42 patients with secundum ASD treated successfully with percutaneous device closure. All patients underwent transthoracic echocardiography examination with tissue Doppler imaging before, 24 hours after and within 3 months of intervention. Measurements of arterial stiffness were carried out using a Mobil‐O‐Graph arteriography system. Results: Remodeling of heart chambers occurred immediately and persisted at 3 months after ASD closure. Significant decreases were observed in right ventricle (RV) end‐diastolic diameter, right atrium volume index, and tricuspid annular plane systolic excursion both after the procedure and at 3 months ( P < .01 for all). The RV and left ventricle (LV) tissue Doppler‐myocardial performance index demonstrated to decline during follow up ( P = .0001). Significant correlations were found between pulse‐wave velocity, augmentation index, pulmonary artery stiffness, and LV‐RV tissue Doppler‐myocardial performance index at third month. Linear regression analyses showed that pulse‐wave velocity is the most effective parameter of LV and pulmonary artery stiffness is the most effective parameter of RV functional recovery, respectively, assessed by tissue Doppler‐myocardial performance index. Conclusions: Percutaneous closure of secundum ASD in adults has various sustained benefits on multiple echocardiographic parameters within 3 months. The changes in RV and LV function after device closure were significantly correlated with the degree of pulmonary artery stiffness and pulse‐wave velocity, respectively.